2012
DOI: 10.1080/19361610.2012.656252
|View full text |Cite
|
Sign up to set email alerts
|

Terrorist Use of Internet: Possible Suggestions to Prevent the Usage for Terrorist Purposes

Abstract: As new developments occur everyday in technology, terrorists are easily adjusting themselves to this change. In this new age of terrorism, terrorism is transnational, institutionalized, technologically advanced, and global. In this respect, today's terrorist organizations are using the Internet for different purposes. The Internet has become the new and main source of communication in terms of disseminating propaganda for terrorist activities. Almost all terrorist organizations are exploiting the Internet for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…The internet is often considered an effective communication tool for terrorist and terrorist groups giving them relative anonymity, a huge amount of information and very cheap connection compared to other communication tools (Benson, 2014;Bowman-Grieve, 2013;Holt et al, 2015;Ogun, 2012;Rudner, 2017;Torok, 2013;Tsfati and Weimann, 2002;Weimann, 2011;Tvaronavičienė, Černevičiūtė, 2015;Hilkevics, Hilkevics, 2017;Štitilis et al, 2016;Limba et al, 2017).…”
Section: The Internet As An Instrument Used By Lone Wolvesmentioning
confidence: 99%
“…The internet is often considered an effective communication tool for terrorist and terrorist groups giving them relative anonymity, a huge amount of information and very cheap connection compared to other communication tools (Benson, 2014;Bowman-Grieve, 2013;Holt et al, 2015;Ogun, 2012;Rudner, 2017;Torok, 2013;Tsfati and Weimann, 2002;Weimann, 2011;Tvaronavičienė, Černevičiūtė, 2015;Hilkevics, Hilkevics, 2017;Štitilis et al, 2016;Limba et al, 2017).…”
Section: The Internet As An Instrument Used By Lone Wolvesmentioning
confidence: 99%
“…The studies by Wittig (2011) and Romaniuk (2014) offered a counter-narrative that challenges the conventional debates regarding TF by exploring other instruments and emergent methods used by terror groups to fund their operations. This position was also advanced by the growing literature and studies that suggest that the advancement in information and communication technology, particularly the internet and its tools, not only provide a platform used by terror groups to recruit and disseminate their propaganda; this also allows them to fund their operations (Carroll & Windle, 2018;Conway, 2006aConway, , 2006bJacobson, 2010;Keene, 2011;Myres, 2012;Ogun, 2012;Organization for Security and Cooperation in Europe, 2017;Theohary, 2011). These studies revealed that terror groups such as Al-Qaeda, Al-Shabaab, Hamas, ISIS, and Mujahideen among other jihadist groups receive funding and support through digital payments from groups and individuals sympathetic to their cause (Ashley, 2012;Basile, 2004;Brill & Keene, 2014;Choo, 2015;Irwin et al, 2014;Levy & Yusuf, 2019;Whyte, 2019).…”
Section: Methodology and Data Collectionmentioning
confidence: 99%
“…Historically, terrorist networks have used various media, and recently, the Internet, as propaganda and recruitment instruments for terrorist activities [12,13,18,30,43,66]. The Internet websites, the globalization of communications via emails, smart phones and tablets, among other ICT tools, and the digitization of media, however, have radically reshaped the structure and capability of terrorism communication.…”
Section: Social Media Use By Terrorist Networkmentioning
confidence: 99%